2022
DOI: 10.1021/acs.est.1c08239
|View full text |Cite
|
Sign up to set email alerts
|

A New Approach to Characterizing the Partitioning of Volatile Organic Compounds to Cotton Fabric

Abstract: Chemical partitioning to surfaces can influence human exposure by various pathways, resulting in adverse health consequences. Clothing can act as a source, a barrier, or a transient reservoir for chemicals that can affect dermal and inhalation exposure rates. A few clothing-mediated exposure studies have characterized the accumulation of a select number of semi-volatile organic compounds (SVOCs), but systematic studies on the partitioning behavior for classes of volatile organic compounds (VOCs) and SVOCs are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 71 publications
2
13
0
Order By: Relevance
“…For instance, the water surface in a sink and the water absorbed in clothes are both indoor water-rich reservoirs. 68 Meanwhile, the organic lm on kitchen surfaces aer cooking and the paint layer of walls can be organic-rich reservoirs indoors. 69,70 From a microscopic perspective, the surface organic lms with the thickness up to tens of nanometers are formed from molecule accumulation over months, and the composition of semi-volatile compounds can be uniform over weeks.…”
Section: Chemical 2d-partitioning Space Plots and Implication To Indo...mentioning
confidence: 99%
“…For instance, the water surface in a sink and the water absorbed in clothes are both indoor water-rich reservoirs. 68 Meanwhile, the organic lm on kitchen surfaces aer cooking and the paint layer of walls can be organic-rich reservoirs indoors. 69,70 From a microscopic perspective, the surface organic lms with the thickness up to tens of nanometers are formed from molecule accumulation over months, and the composition of semi-volatile compounds can be uniform over weeks.…”
Section: Chemical 2d-partitioning Space Plots and Implication To Indo...mentioning
confidence: 99%
“…A similar inverse relationship between log(K ca ) and vapor pressure has also been observed for PDBEs and VOCs. 37,54 Further, we observed an inverse relationship between log(K ca ) for all neutral PFAS except EtFOSA and indoor temperature, indicating that these species favor the gas phase over the cloth at elevated temperatures (Section S7; Figures S12 and S13). Although the correlations are modest, they are significant (95% confidence interval) for 6:2 FTOH and MeFOSE, with R 2 values of 0.24 and 0.55 and p values of 0.0152 and 0.0002, respectively.…”
Section: ■ Results and Discussionmentioning
confidence: 82%
“…Previous studies have shown positive correlations between log(K ca ) and log(K oa ) for polybrominated diphenyl ethers (PBDEs), 35,37 phthalates, some PCBs, 35,38 and homologous series of VOCs. 54 However, in these cases, log(K ca ) was either below the 1:1 line (for PBDEs, phthalates, and PCBs) or above the 1:1 line (for VOCs; Figure S10). Five of the six neutral PFAS log(K ca ) values increase with log(K oa ); the log(K ca ) values of MeFOSE and EtFOSE are nearly identical despite an evident, yet small, difference in log(K oa ).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Since the material–phase diffusion models and material–air partition coefficients ( K m‑a , eq S1) for LCMs were absent, the empirical models for other anthropogenic semivolatile organic compounds (SVOCs) with similar physiochemical properties, such as polycyclic aromatic hydrocarbons (PAHs) and polybrominated diphenyl ethers (PBDEs), could be used as references. , The diffusion-partitioning of LCMs from LL to LGP and SP was estimated by using two modeling methods.…”
Section: Methodsmentioning
confidence: 99%